Modelling of the effect of ELMs on fuel retention at the bulk W divertor of JET. (May 2019) - Heinola, K.; Ahlgren, T.; Brezinsek, S.; Vuoriheimo, T.; Wiesen, S.; ,
Highlights: Effect of ELMs on fuel retention at the bulk W target of JET-ILW was studied with multi-scale calculations. Energetic intra-ELM Deuterium particles get implanted and create near-surface defects up to depths of few tens of nm, which act as the main fuel trapping sites during ELMs. Inter-ELM Deuterium particles increase the filling levels of trapped fuel in defects. Clustering of vacancies was found to take place at high temperatures. Abstract: Effect of ELMs on fuel retention at the bulk W target of JET ITER-Like Wall was studied with multi-scale calculations. Plasma input parameters were taken from ELMy H-mode plasma experiment. The energetic intra-ELM fuel particles get implanted and create near-surface defects up to depths of few tens of nm, which act as the main fuel trapping sites during ELMs. Clustering of implantation-induced vacancies were found to take place. The incoming flux of inter-ELM plasma particles increases the different filling levels of trapped fuel in defects. The temperature increase of the W target during the pulse increases the fuel detrapping rate. The inter-ELM fuel particle flux refills the partially emptied trapping sites and fills new sites. This leads to a competing effect on the retention and release rates of the implanted particles. At high temperatures the main retention appeared in larger vacancy clusters due to increased clustering rate.